Addressing gaps in : TVET Ecosystems - Saat, Shakir (Akademi Kepimpinan Pendidikan Tinggi (AKEPT), 2024)
Emerging from the influential seminar Addressing Gaps in TVET Ecosystems, this book represents a collaborative effort between the Higher Education Leadership Academy (AKEPT) and Universiti Teknikal Malaysia Melaka (UTeM). Aimed at capturing the essence and outcomes of this landmark event, the book sets out to explore the dynamic realm of TVET Ecosystems in Malaysia. It is designed to serve as an indispensable resource for stakeholders across the educational, policy makers and industrial spectrum, shedding light on the imperative need for reform and the potential pathways forward in TVET Photo source: AKEPT website The narrative within these pages delves deep into the core challenges confronting TVET ecosystems, as highlighted in the seminar. Through a blend of keynote addresses, in- depth forums, and vivid success stories, it articulates a vision for a revamped, more resilient TVET framework. The discourse encompasses the urgent need for integrating technology in educational strategies and showcases innovative solutions that promise to redefine TVET Education overall. By doing so, it addresses critical gaps in the current system and proposes actionable strategies for bridging these divides, aiming to inspire renaissance in TVET education that aligns with global advancements and market demands. Crafted by experienced educators, researchers, and practitioners, the content of this book stands as a testament to the wealth of expertise and passion driving the TVET reform agenda. Each contributor brings a unique perspective, enriching the discussion with insights drawn from the forefront of educational innovation. This book, therefore, is not just a reflection of a seminar but a beacon for all dedicated to the advancement of TVET, encapsulating the collective wisdom of those at the helm of change. In essence, it offers a roadmap for transforming TVET into a cornerstone of sustainable development and societal progress.